Married Women and Businesses - Chambers, Lori (Ontario History, 2012)
Married women's property law reform in the nineteenth century made it legally possible for wives to run businesses independently of husbands. However, marital property law reform as interpreted by the courts of Ontario still conceptualized the wife as a dependent partner in marriage who owed labour and services to her husband. A woman's ability to run a business on her own account was limited by the rules assigned to married women's property ownership, and her labour in a family business was constructed as a labour of love, performed for the benefit of family, and to the profit of her husband. Women faced significant challenges in obtaining credit and maintaining ownership of enterprises. By examining Ontario cases in which wives sought to control the assets from their businesses, this paper explores the limitations of reform, and asserts not only that business is not gender neutral, but also that understanding law is essential to understanding why women have been marginalized in the business community and business history.